Sexual Function, Sexual Activity and Quality of Life in Women with Ovarian and Endometrial Cancer - Harter, P.; Schrof, I.; Karl, L. M.; Hils, R.; Kullmann, V.; Traut, A.; Scheller, H.; du Bois, A. (Geburtshilfe und Frauenheilkunde, 2013)
Background: Gynecological cancer (GC) is assumed to have an impact on sexual function and activity, but pertinent evidence is currently limited. Patients and Methods: Sexual function and activity were investigated in patients with gynecological cancer (GC) and in a control group (C), using the “Sexual Activity Questionnaire” (SAQ), the “Female Sexual Function Index” (FSFI), and parts of the EORTC QLQ-C30. Results: 727 women (335 GC and 392 C) were given a questionnaire and 22.8 % of them responded. Response rates were equivalent for both groups (23.6 % [GC] and 22.2 % [C]). 51.5 % (C) and 59.5 % (GC) were not sexually active, mainly owing to lack of a partner (37 %) or lack of interest (21 %) (C group), and lack of interest (40 %, p < 0.05), physical problems (31.9 %, p < 0.05), and physical problems suffered by their partner (21 %, p < 0.05) (GC group). There were significant differences between both groups in the SAQ discomfort score (p < 0.05), but no significant differences in quality of life or other scores for sexuality. Conclusion: The quality of sexuality tends to be impaired in GC patients, but this does not appear to influence quality of life. A shift in priorities caused by the considerable anxiety about surviving the cancer might explain our findings.
Keywords: ovarian cancer; endometrial cancer; dyspareunia